The periodontal health of post-orthodontic subjects - Staples Glenn; Freer Terrence J.; Basford Kaye (Australasian Orthodontic Journal, 1987)
It has been hypothesised that orthodontic treatment is an important factor in the aetiology of periodontal disease. To test this hypothesis it was desirable to match the control group and the study group on dental awareness, plaque score and sulcus bleeding as these factors may mask the effects of orthodontic treatment. In the present investigation the study group comprised 83 subjects with an average age of 21.1 years while the control group comprised 33 subjects with an average age of 19.7 years. Intra-examiner and inter-examiner variability were tested. Differences between examiners in measuring pocket depths never exceeded one millimetre.